Dampak Penggunaan Peradilan Formal Dalam Penyelesaian Tindak Pidana Ringan Dan Alternatif Penyelesaiannya - Sahabuddin, S.; Zulfikar, Ahmad (Universitas Batanghari Jambi, 2023)
Criminal policies carried out through formal justice have given rise to various criticisms in society, especially towards minor crimes (TIPIRING), because the use of formal criminal justice in TIPIRING has an impact, both on relations between parties, on society and on state expenditure. Taking into account that formal judicial power is in the hands of the state and in social reality there is a resolution of minor crimes carried out by the community based on local wisdom and international developments that require the use of restorative justice in resolving crimes, the idea of a reintegrative resolution for minor crimes was raised. This reintegrative model is a rational effort to resolve minor crimes by utilizing local wisdom together with the structure of the criminal justice system and is based on the principles of restorative justice. The concept promoted by the reintegrative model is to repair damaged relationships as a result of criminal acts. The work pattern does not use criminal justice (non-penal), but rather brings together the parties involved in minor crimes, and the resolution uses mediators or facilitators. Through a normative type of research with a concept and principle approach, it is hoped that concrete understanding results can be obtained that this issue is interesting to discuss.